Pengaruh Tuntutan Pekerjaan Terhadap Keterikatan Kerja Melalui Burnout (Studi Pada Tim Penguji Kendaraan Dinas Perhubungan Kota Pasuruan) - Halim, Gunawan (SINOMIKA Journal: Publikasi Ilmiah Bidang Ekonomi dan Akuntansi, 2022)
The purpose of this study was to determine the effect of job demand on work engagement mediated by burnout at the Pasuruan City Transportation Department. Job demand refers to the physical, psychological, social, and organizational aspects of work that require psychological (cognitive and emotional) and physical resilience to complete the task. Work engagement is a combination of three concepts, namely job satisfaction, commitment to the organization, and extra behavior, namely discretionary efforts that go beyond the tasks of one's own work. While burnout is a syndrome of fatigue, both physically and mentally which includes developing a negative self-concept, lack of concentration and negative work behavior. This research is a quantitative method using a questionnaire from 40 respondents as the total sample from the otor vehicle testing division at the Pasuruan City Transportation Department. According to the results of this study, job demands have a positive and insignificant effect on work engagement, job demands have a positive and significant effect on burnout, burnout has a positive and insignificant effect on work engagement, and burnout cannot mediate the effect of job demands on work engagement.